2012
DOI: 10.2138/am.2012.4039
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure study of a natural cancrinite

Abstract: The high-pressure elastic behavior and the P-induced structure evolution of a natural cancrinite from Cameroun {Na 6.59 Ca 0.93 [Si 6 Al 6 O 24 ](CO 3 ) 1.04 F 0.41 ·2H 2 O, a = 12.5976(6) Å, c = 5 .1168(2) Å, space group: P6 3 } were investigated by in situ single-crystal X-ray diffraction under hydrostatic conditions up to 6.63(2) GPa with a diamond-anvil cell. The P-V data were fitted with an isothermal Birch-Murnaghan type equation of state (BM EoS) truncated to the third order. Weighted fit (by the uncert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 45 publications
5
25
0
Order By: Relevance
“…The in-situ high-temperature X-ray diffraction experiment was performed on a crystal fragment (size 300 x 200 x 150 μm 3 ), from the main batch already used by Della Ventura et al (2009 and Lotti et al (2012), showing sharp optical extinction with crossed polarized light under the microscope. The previous diffraction studies reported no superstructure reflections.…”
Section: -Sample Preparationmentioning
confidence: 99%
See 4 more Smart Citations
“…The in-situ high-temperature X-ray diffraction experiment was performed on a crystal fragment (size 300 x 200 x 150 μm 3 ), from the main batch already used by Della Ventura et al (2009 and Lotti et al (2012), showing sharp optical extinction with crossed polarized light under the microscope. The previous diffraction studies reported no superstructure reflections.…”
Section: -Sample Preparationmentioning
confidence: 99%
“…In order to get a stable refinement, some restraints were applied: i) the Na2/Ca2 site was refined applying a mixed Na/Ca X-ray scattering curve and constraining their fractions to sum full occupancy (a test refinement with occupancy factors free to vary validated this as a good approximation, i.e. within 2); ii) the C1-OC1 and C2-OC2 bond distances were restrained to 1.300(5) Å following a previously reported procedure Lotti et al 2012); iii) the C1-C2 and OC1-OC2 sites were constrained to share the same displacement parameters (dp's), respectively. Convergence was achieved in the last cycles of refinement with anisotropic dp's for all the sites, excluding Ow.…”
Section: -Structure Refinementsmentioning
confidence: 99%
See 3 more Smart Citations